Strategi Optimalisasi Penyerapan Anggaran pada Sekretariat Daerah Kota Depok - Kaharuddin, Amalyah; Hakim, Dedi Budiman; Falatehan, Faroby (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2024)
The purpose of this study is to identify and analyze the pattern of budget absorption quarter, analyze the causes of non-optimal budget absorption and formulate alternative strategies  in  optimizing  budget  absorption  at  the  Depok  City  Regional   Secretariat. Respondents were determined by purposive sampling by including elements of planners, activity/financial managers, supervisors and representatives of the scope of the Regional Secretariat as well as experts in the formulation of alternative optimization strategies. Analysis method with gap analysis to identify patterns of budget absorption per quarter, to analyze the causes of budget absorption delays with likert scale analysis and AHP (Analitycal Hierarchy Process) in the formulation of alternative strategies. The pattern of budget absorption at the Regional Secretariat of Depok City in the research period from 2015 to 2021 tends to be the same, namely high at the end of the year / quarter IV and low at the beginning of the year / quarter I. With the average budget absorption in the fourth quarter is 40.30%, while in the first, second, third quarters respectively are: 7.33%, 18.39%, 21.35%. This is inversely proportional to the average cash plan prepared which is high at the beginning of the year and low at the end of the year. Meanwhile, the average absorption of the direct expenditure budget of the Depok City Regional Secretariat is 87.37%. From the results of primary data processing, it was found that the main cause of not optimal budget absorption at the Regional Secretariat was coordination of cash budget preparation that had not been effective / only carried out by financial managers / operators causing budget absorption not in accordance with the cash budget plan. From hasil AHP using Expert Choice 11 shows that the main factor that has not been optimal budget absorption is the Internal Control System with a value of 0.453, then the Actor with the greatest priority is the Head of Section as the Budget User Power (KPA) (0.297). The main obstacle obtained is that Control and Supervision is not optimal (0.395). Meanwhile, the main alternative strategy is the optimization of internal monev in a tiered and periodic manner.